Microstructural evolution and geometrical properties of TiB2 metal matrix composite protrusions on hot work tool steel surfaces manufactured by laser implantation - Spranger, Felix; de Oliveira Lopes, Marcelo; Schirdewahn, Stephan; Degner, Julia; Merklein, Marion; Hilgenberg, Kai (International Journal of Advanced Manufacturing Technology, 2019)
The laser implantation–named technique aims to address the tribological problems frequently seen on tool surfaces during hot stamping. It is based on the creation of elevated dome- or ring-shaped hard structures on the surface of tool steels by a localized dispersing of hard particles. Therefore, a combination of the two distinct approaches that are normally used in surface technology for optimizing friction and wear, i.e., surface texturing and surface material optimization, are realized in one processing step. In experimental studies, a localized dispersing of TiB2 particles in the surface layer of the hot work tool steel X38CrMoV5-3 was considered and compared with punctual laser–remelted textures. The structures (micro-) hardness was measured at top- and cross-sections. With the aid of a scanning electron microscope, energy dispersive X-ray spectroscopy and X-ray diffraction the interaction between the hard particles and the substrate material were studied. From the results, an optimal parameter range was identified for laser implantation. To the investigation’s end, the implant geometry was measured by optical microscopy and white light microscopy. Furthermore, a mathematic model was introduced, which allows a prediction of the implant geometry as a response to the laser parameters. It was shown that the implantation of TiB2 particles leads to a significant hardness increase up to 1600 HV1 due to the dispersion of initial particles and an in situ precipitation of new titanium-rich phases. It was possible to create defect-free dome- and ring-shaped microstructures on the surfaces. It was also shown that the implants geometry highly depends on the applied laser parameters. The applied central composite design shows a good agreement with the experimental results.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Hot stamping; Hot work tool steel; Laser implantation; Localized laser dispersing; Surface texturing; TiB2